Pengaruh Pemberian Pupuk Guano dan Dolomit terhadap Ketersediaan Unsur Hara Posfor pada Tanah Podsolik - Indah Apriliana Puspitasari; Meldia Septiana; Fakhrur Razie (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2023)
Podzolic soils have various problems including acidity of the soil (pH) and low soil nutrient content. This study aims to determine the effect of guano and dolomite on the availability of P nutrients in podsolik soils, and to determine the best treatment. This study was a pot experiment using a completely randomized design (CRD) with one factor, namely (P1 = Dolomite 2 t ha-1); (P2 = Guano Fertilizer 0,5 t ha-1); (P3 Guano Fertilizer 0.5 t ha-1 and Dolomite 2 t ha-1); (P4 = Guano Fertilizer 1 t ha-1 and Dolomite 2 t ha-1); (P5 Guano Fertilizer 1.5 t ha-1 and Dolomite 2 t ha-1). Each treatment was repeated 4 times, so there were 24 experimental units. The results showed that the application of dolomite and guano fertilizers had an effect on the available-P, pH, Exchangable Ca and Exchangable Al. However, it has no effect on Mg-dd in Podzolic soil. The application of dolomite and guano fertilizer with a dosage of 0.5 t ha-1 guano fertilizer and 2 t ha-1 dolomite was the best result for the availability of P, Exchangable Ca and pH.